HIV Disease Dynamics and Markers of Inflammation and CNS Injury During Primary HIV Infection and Their Relationship to Cognitive Performance. (1st February 2022) - Longino, August A.; Paul, Robert; Wang, Yixin; Lama, Javier R.; Brandes, Peter; Ruiz, Eduardo; Correa, Cecilia; Keating, Sheila; Spudich, Serena S.; Pilcher, Christopher; Vecchio, Alyssa; Pasalar, Siavash; et al.
Abstract : Introduction: Early systemic and central nervous system viral replication and inflammation may affect brain integrity in people with HIV, leading to chronic cognitive symptoms not fully reversed by antiretroviral therapy (ART). This study examined associations between cognitive performance and markers of CNS injury associated with acute HIV infection and ART. Methods: HIV-infected MSM and transgender women (average age: 27 years and education: 13 years) enrolled within 100 days from the estimated date of detectable infection (EDDI). A cognitive performance (NP) protocol was administered at enrollment (before ART initiation) and every 24 weeks until week 192. An overall index of cognitive performance (NPZ) was created using local normative data. Blood (n = 87) and cerebrospinal fluid (CSF; n = 29) biomarkers of inflammation and neuronal injury were examined before ART initiation. Regression analyses assessed relationships between time since EDDI, pre-ART biomarkers, and NPZ. Results: Adjusting for multiple comparisons, shorter time since EDDI was associated with higher pre-ART VL and multiple biomarkers in plasma and CSF. NPZ scores were within the normative range at baseline (NPZ = 0.52) and at each follow-up visit, with a modest increase through week 192. Plasma or CSF biomarkers were not correlated with NP scores at baseline or after ART. Conclusions: Biomarkers of CNS inflammation, immune activation, and neuronal injury peak early and then decline during acute HIV infection, confirming and extending results of other studies. Neither plasma nor CSF biomarkers during acute infection corresponded to NP scores before or after sustained ART in this cohort with few psychosocial risk factors for cognitive impairment.